(untitled) - Boyd, Robert (New York, 2003)
The book explained things well and actually made complex biological concepts simple to understand, even for a undergraduate. It provides a very detailed and easy to understand overview of human evolution and the biology of human culture.
Keywords: Human evolution,Tiến hóa con người